TEKNOLOGI KOMUNIKASI DAN PERILAKU REMAJA - Ana Puji Astuti; Anike NUrmalita Rps (UNIVERSITAS SEBELAS MARET (UNS), 2014)
Every culture has knowledge, science and technology, which used as areference for interpreting and understanding the environment and itscontents, and used as a tool to exploit, process and use it to satisfy humanneeds. Communication of technology development is very fast at all. Withthe development of science and technology people get various facilities incarrying out daily activities. Even as now almost every person can not beseparated from the communication technologies, as experienced by youngpeople today. Adolescence is a period of transition from children to adultswho are beginning to be affected by the environment and have a willingnessto be what he wants himself. With the advances in communicationtechnology spur teens to more intensive self-seeking activities by looking atfigures in the media. Keywords: Teknology, behavior, youth.